Polyamine‐independent growth and biofilm formation, and functional spermidine/spermine N‐acetyltransferases in Staphylococcus aureus and Enterococcus faecalis. Issue 1 (4th November 2018) - Li, Bin; Maezato, Yukari; Kim, Sok Ho; Kurihara, Shin; Liang, Jue; Michael, Anthony J.
Summary: Polyamines such as spermidine and spermine are primordial polycations that are ubiquitously present in the three domains of life. We have found that Gram‐positive bacteria Staphylococcus aureus and Enterococcus faecalis have lost either all or most polyamine biosynthetic genes, respectively, and are devoid of any polyamine when grown in polyamine‐free media. In contrast to bacteria such as Pseudomonas aeruginosa, Campylobacter jejuni and Agrobacterium tumefaciens, which absolutely require polyamines for growth, S. aureus and E. faecalis grow normally over multiple subcultures in the absence of polyamines. Furthermore, S. aureus and E. faecalis form biofilms normally without polyamines, and exogenous polyamines do not stimulate growth or biofilm formation. High levels of external polyamines, including norspermidine, eventually inhibit biofilm formation through inhibition of planktonic growth. We show that spermidine/spermine N ‐acetyltransferase (SSAT) homologues encoded by S. aureus USA300 and E. faecalis acetylate spermidine, spermine and norspermidine, that spermine is the more preferred substrate, and that E. faecalis SSAT is almost as efficient as human SSAT with spermine as substrate. The polyamine auxotrophy, polyamine‐independent growth and biofilm formation, and presence of functional polyamine N ‐acetyltransferases in S. aureus and E. faecalis represent a new paradigm for bacterial polyamine biology. Abstract : Distantly related functional spermidine/spermine N ‐acetyltransferases are encoded by Staphylococcus aureus USA300 and Enterococcus faecalis that in principle reduce the cellular toxicity of spermidine and spermine. However, neither S. aureus USA300 nor E. faecalis produce polyamines and can grow and form biofilms normally in the complete absence of polyamines, suggesting that the spermidine/spermine N ‐acetyltransferases function solely to acetylate externally acquired spermidine and spermine. These findings illuminate a new paradigm in bacterial polyamine physiology.